Deposition of alginate-oregano nanofibres on cotton gauze for potential antimicrobial applications - Orisawayi, Abimbola Oluwatayo; Lu, Hao; Badruddin, Ishrat Jahan; Venkatraman, Prabhuraj D.; Britten, Nicole S.; Butler, Jonathan A.; Koziol, Krzysztof K.; Rahatekar, Sameer S. (Elsevier, 2025)
In this study, we developed an innovative natural antibacterial medical bandage composed of electrospun nanofibres derived from alginate (SAg) and oregano essential oil (OEO). The nanofibre deposition process was systematically optimised, achieving a controlled evolution of fibre formation at intervals of 1, 2, 3, 4, and 8 h. Over time, fibre morphology has changed from a dispersed network to a densely packed, homogeneous, fibrous, fully embedding cotton gauze nanofibre. Scanning Electron Microscopy (SEM) revealed nanofibres with diameters ranging from 100 to 300 nm, 46 % measuring 100–200 nm, 37 % at 200–300 nm, and 14 % between 300 and 400 nm. Thermogravimetric Analysis (TGA) confirmed improved thermal stability in cross-linked samples. At the same time, Fourier Transform Infrared Spectroscopy (FTIR) shows the incorporation of OEO into the nanofibres shows OEO carvacrol, and thymol. Antibacterial efficacy tested inhibition zone assays against Methicillin-resistant Staphylococcus aureus (MRSA) and Listeria monocytogenes on double-layered bandages is 15 mm and 10 mm, respectively. Statistical analysis results from ANOVA confirmed that multi-layered bandages (TL-BSS) had significantly enhanced antibacterial activity compared to single-layered (SSS) and both-sided spun (BSS) configurations. Unlike conventional wound dressings, this study introduces a bioactive, nanofibre-integrated gauze with sustained antibacterial efficacy.
Corrigendum to “Deposition of alginate-oregano nanofibres on cotton gauze for potential antimicrobial applications” [Int. J. Biol. Macromol. Vol. 319 (2025), 1-16 Article 145, 372]. International Journal of Biological Macromolecules, Volume 319, Pt 4, August 2025, Article number 146240
Keywords: 3101 Biochemistry and Cell Biology; 31 Biological Sciences; Emerging Infectious Diseases; Infectious Diseases; Polymers; Electrospinning; Nanofibre; Alginate; Oregano essential oil; Antibacterial bandages